A practical approach to using the IMS-QTI specification. (1st January 2012) - Auzende, Odette; Giroire, Hélène; Le Calvez, Françoise
The advent of the web has deeply modified educational practices. Teachers and learners like having many exercises available for training or for assessing. A solution to this is to allow many authors to create and share resources; this involves gathering together several communities using the same format. A study of the most used LMSs has shown that IMS-QTI is the most accomplished specification to express interactive and parameterised exercises. Moreover, to ensure that instantiated exercises have the same level of difficulty, it is necessary to define constraints between parameters. But IMS-QTI is limited here. Therefore, we have extended IMS-QTI to express the constraints between interdependent parameters. To validate this approach, we have implemented tools for teachers: an editor for creating interactive exercises with constrained parameters and feedback; a translator of IMS-QTI files to play interactive exercises on the web without web services; a classification for storing the exercises. The proposed extensions have been agreed by the IMS-QTI group.